Double Burden and Social Stigma: A Case Study of Bullying Among Working Students at State Senior High School 1 Peusangan, Bireuen, Indonesia - Zahriyanti; Musrizal; Ikhwani; Muhammad Iqbal (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Working students from economically disadvantaged backgrounds frequently face challenges that extend beyond balancing education and employment, including negative social perceptions and unequal treatment within school communities. Although school bullying has been widely investigated, limited attention has been paid to how the combination of double burden and social stigma shapes the experiences of working students in secondary education. This study explores the dynamics of bullying encountered by working students at State Senior High School 1 Peusangan, Bireuen, Indonesia. A qualitative case study approach was employed, drawing on data collected through classroom observations, in-depth interviews, and document analysis involving school leaders, teachers, counselors, and students selected purposively. Data were interpreted using the interactive analytical framework of Miles, Huberman, and Saldaña, while source triangulation was applied to strengthen the credibility of the findings. The analysis revealed that the simultaneous demands of schooling and manual work increased students' susceptibility to stigmatization, verbal humiliation, physical intimidation, and social exclusion. Moreover, bullying was often perceived as ordinary peer interaction, reducing institutional awareness and delaying appropriate responses. These findings indicate that bullying against working students reflects broader patterns of socioeconomic inequality rather than isolated interpersonal conflict. The study emphasizes the need for school policies and educational practices that foster empathy, strengthen institutional responsiveness, and create more inclusive learning environments for economically marginalized students.